Quantitative Analysis of Phytochemical Constituents and Antioxidant Efficiency of Cucumis prophetarum L. - Kolar, Firdose R.; Mujawar, Saleha M.; Lamani, Babu R. (Free Radicals and Antioxidants)
Background: The current study evaluated the efficiency of different solvent extractions on the yield of total phenolics and flavonoid content as well as antioxidant activity for different plant parts (root, stem, leaves, immature and mature fruits) of Cucumis prophetarum. Materials and Methods: The antioxidant activity of the extracts was assessed by using the following methods: Ferric reducing antioxidant power assay (FRAP assay), ferrous ion chelating activity, phosphomolybdenum reducing power assay and hydrogen peroxide radical scavenging assay. Results: The chemical examination of comparative extractive solvents of different plant parts (root, stem, leaves, immature and mature fruits) showed variations in the amount of active ingredients under investigation. Among the different plant parts analyzed for phenolics and flavonoid content, the aqueous extract of leaf material yielded highest content of phenolics (22.6 mg TAE/g dry weight) and flavonoids (3.15 mg RE/g dry weight) as compared to other plant parts. The aqueous extracts rich in phenolics and flavonoid content also exhibited potent antioxidant activity in all the assays and showed expected significant positive correlation with the phytochemical compounds. Conclusion: The study indicated that in phenolics, flavonoids and antioxidant assays, the results were higher for aqueous extraction system than other extragents used. Hence, the aqueous extract represents a source of potential antioxidants that could be used in pharmaceuticals.
Keywords: Cucumis prophetarum; Cucurbitaceae; Phenolics; Flavonoids; Free radicals; Correlation